PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT NUSATRIP JAKARTA SELATAN - Submission JORAPI; Trimo Fajar Juliadi; Syarifah Ida Farida (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of communication and work environment on employee performance at PT. Nusatrip South Jakarta. The method used in this research is quantitative. The sampling technique used is saturated sampling where the entire population becomes the sample in the study, which consists of 74 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The result of this study is communication (X1) and work environment (X2) on employee performance (Y) obtained from the linear regression equation Y=5.807 + 0.464X1 + 0.291X2. The correlation value or the degree of relationship between the independent variable and the dependent variable is 0.812, indicating a strong relationship. The coefficient of determination value or the contribution of its influence simultaneously is 65.9%. The partial hypothesis test obtained a communication value of tcount 10.472 > ttable 1.993, thus Ho1 is rejected and Ha1 is accepted, indicating that there is a positive and significant influence of work communication on employee performance. The work environment value is tcount 9.828 > ttable 1.993, thus Ho2 is rejected and Ha2 is accepted, indicating that there is a positive and significant influence of the work environment on employee performance. The Fcount hypothesis test value is 68.531 > Ftable 3.12, thus Ho3 is rejected and Ha3 is accepted, meaning that simultaneously there is a positive and significant influence of communication and the work environment on employee performance at PT. Nusatrip Jakarta Selatan.